KOMERSIALISASI LAHAN PERTANIAN DI KOYA BARAT DAN KOYA TIMUR, KOTA JAYAPURA - Yusuf, Muhammad; Sahudi, Sahudi; Muhandy, Rachmad Surya (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
This paper aims to find out about the commercialization of agricultural land, and the current model of agricultural land commercialization in West Koya and East Koya, and the Jayapura City’s goverment attitude toward the lack of agricultural land in Jayapura City area. This is a qualitative research, using a social phenomenology paradigm. The results showed that the increasingly dense population of Jayapura City has led in the expansion of the city towards Koya region which is suburb area. Smooth transportation facilities and good infrastructure make Koya region more evolving. The land price in Koya area depends on the sale value of tax object, it is also influenced by the lack of land used as a place to live due to the density increasing of urban area so that the resident seek residential land in Koya area. Transmigrants or farmers who have no knowledge basis in agriculture, and have difficulty dealing with rice pests, causing them to be reluctant to plant rice, and difficult to adapt to the environmental situation. Farmers are more benefited by converting the farmland to fishery land. By utilizing former farmland to be used as a public fishing pond as amusement or tourism place. The economic pressure of community at the beginning of transmigration program was a heavy burden that felt by them, while the needs as supporting tools were hard to find. The high cost of living is the cause of transmigrants’ inability to survive, therefore, they decided to leave their transmigration land by selling it to a second party.